1989
DOI: 10.1677/joe.0.1210331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal hypothyroxinaemia during fetal life on the calmodulin-regulated phosphatase activity in the brain of the adult progeny in the rat

Abstract: Calmodulin-regulated phosphatase activity was measured in the brain of 2-month-old rats born from hypothyroid and normal dams, using a fluorometric enzyme assay developed for this purpose. Calmodulin content was measured in the same brain regions by radioimmunoassay. Significant differences between groups in weight and protein content, basal phosphatase and calmodulin-regulated phosphatase activity were found. The brain region most affected was the cerebellum, where basal and calmodulin-regulated phosphatase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Elevated calmodulin may also act on membrane proteins, second messenger pathways, and metabolic pathways. These results are consistent with previous observations that may link depressed levels of brain T3 (triiodothyronine) in the progeny of maternal hypothyroidism (Porterfield and Hendrich,199 1) with increases in calmodulin-related phosphatase activity in the brains of these progeny (Ruiz de Elvira et al, 1989).…”
Section: Scb Transport Of Actin and Spectrin In Hypothyroid And Euthysupporting
confidence: 92%
“…Elevated calmodulin may also act on membrane proteins, second messenger pathways, and metabolic pathways. These results are consistent with previous observations that may link depressed levels of brain T3 (triiodothyronine) in the progeny of maternal hypothyroidism (Porterfield and Hendrich,199 1) with increases in calmodulin-related phosphatase activity in the brains of these progeny (Ruiz de Elvira et al, 1989).…”
Section: Scb Transport Of Actin and Spectrin In Hypothyroid And Euthysupporting
confidence: 92%
“…Neurobiological and behavioural effects of maternal hypothyroxinaemia during pregnancy in animal models have been definitely elucidated in rats in numerous studies (Ruiz de Elvira et al, 1989;Hadjzadeh et al, 1990;Sinha et al, 1992;Attree et al, 1992) and in the sheep (Hetzel & Potter, 1983;Potter et al, 1986). Therefore, maternal thyroid hormone transfer to the fetus, previously denied or considered of minimal relevance (Fisher & Klein, 1981;Roti et al, 1983) but recently demonstrated in rats (Escobar del Rey et al, 1986;Woods et al, 1984) and inman (Vulsma et al, 1989) appears to be of critical importance in intrauterine brain development.…”
Section: Dlscurslonmentioning
confidence: 99%
“…The administration of serum from rats with either hypothyroidism or hyperthyroidism induces malformations in rat-embryo cultures in vitro 51 . Finally, the progeny of pregnant rats with hypothyroidism, when studied as adults, have abnormalities in brain amino acid metabolism, marker enzymes of neuronal and glial cells, and calmodulin-regulated phosphatase activity, although postnatal growth and brain weight are not altered 52,53,54 .…”
Section: Effects Of Thyroid Hormone On the Fetus And Neonatementioning
confidence: 99%